Effects of structure and humidity on friction and wear properties of carbon fiber reinforced epoxy composites - Shim, H.H.; Kwon, O.K.; Youn, J.R. (Annual Technical Conference - ANTEC, Conference Proceedings, 1991)
In this study, friction and wear behavior of unidirectional high modulus carbon fiber reinforced epoxy composite exposed to high and low humidity was experimentally examined with various sliding speeds. By considering microstructure of fibers, influence of water content on friction and wear behavior of graphite, and macrostructure of the composite with the experimental results, following conclusions are obtained. Friction and wear behavior of the unidirectional high modulus carbon fiber reinforced epoxy composite; (1) is greatly influenced by the water content at the sliding surface and the water content at the sliding surface is reduced either by low humidity of air or by desorption due to friction temperature increasing with sliding speed. (2) is greatly influenced by the microstructural anisotropic properties caused by the orientation of graphite crystals in the carbon fibers. For example, in the case of transverse direction where graphite crystals in the fibers can be easily oriented parallel to the sliding surface, friction coefficient is comparatively low. On the other hand, in the case of normal direction where graphite crystals in the fibers are oriented normal to the sliding surface, the crystals will shear difficultly and plough the counterface. As the result, the fibers will easily cut out the transfer film on the counterface and damage the counterface. (3) is also influenced by the macrostructural anisotropy caused by fiber orientation with respect to the sliding direction. For example, since the fibers in longitudinal orientation have higher possibility of longer real contact sliding length than transverse orientation, the flash temperatures at real contact areas will be higher than the transverse case, which leads to higher wear.